Sequenciamento de exomas para identificação de variantes genéticas relacionadas ao desenvolvimento do ceratocone em uma família brasileira - Guimarães, Lislie Vitória Rodrigues (Universidade Federal de São Carlos, 2025)
Keratoconus is a degenerative ophthalmological disorder characterized by progressive ectasia of an inflammatory, bilateral, and multifactorial nature, affecting corneal curvature and leading to irregular astigmatism. It occurs in both men and women of all ethnicities, with a global incidence of 1 case per 2,000 births per year and 1.4 per 2,000 in Brazil. Its pathogenesis typically begins in adolescence in an asymptomatic manner, often being mistaken for simple astigmatism, and the only means of early diagnosis comes from corneal imaging exams. In their absence, the clinical condition progresses, resulting in a significant decline in the patient’s visual acuity. Environmental, systemic, and genetic factors are directly associated with the manifestation of keratoconus, and so far, few studies have explored the investigation of affected families through exome sequencing. Moreover, it is important to highlight that the heterogeneity of the Brazilian cohort represents a relevant genotypic and phenotypic model for studies on keratoconus. Thus, this genetic diversity enhances the potential for identifying DNA variants related to the disease, emphasizing the need for further research to improve the understanding of its pathophysiology and mechanisms. In this context, the objective of this study is to investigate the genetic bases involved in the etiology of keratoconus through exome sequencing and risk prediction analysis in Brazilian families, aiming to identify and characterize candidate genes involved in biological pathways related to the pathogenesis and pathophysiology of this ocular condition, and to develop a deeper understanding of the genetic foundations underlying its etiology in Brazil.
Exome sequencing to identify genetic variants related to keratoconus development in a Brazilian family
Keywords: Ceratocone; Sequenciamento de Exomas; Bioinformática; Keratoconus; Exome sequencing; Bioinformatics; CIENCIAS BIOLOGICAS::GENETICA; 3. Saúde e Bem-Estar